2022
DOI: 10.3389/fcvm.2022.774627
|View full text |Cite
|
Sign up to set email alerts
|

Role of N6-methyladenosine Modification in Cardiac Remodeling

Abstract: Cardiac remodeling is the critical process in heart failure due to many cardiovascular diseases including myocardial infarction, hypertension, cardiovascular disease and cardiomyopathy. However, treatments for heart failure focusing on cardiac remodeling show relatively limited effectiveness. In recent decades, epitranscriptomic modifications were found abundantly present throughout the progression of cardiac remodeling, and numerous types of biochemical modifications were identified. m6A modification is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“… 41 , 42 , 43 It has been reported that m 6 A plays an important role in cardiovascular diseases, not only as a biomarker in diagnosis of MI, but also as a medicine in treatment of cardiac remodeling. 44 , 45 Shi et al 44 used comprehensive analysis of m 6 A regulators expression to identify distinct molecular subtypes of MI, and they found several genes were significantly related to the development of MI, with being regulated by m 6 A methyltransferases. In the present research, we also observed the differences in m 6 A modification in MeRIP of MI and sham control tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 , 43 It has been reported that m 6 A plays an important role in cardiovascular diseases, not only as a biomarker in diagnosis of MI, but also as a medicine in treatment of cardiac remodeling. 44 , 45 Shi et al 44 used comprehensive analysis of m 6 A regulators expression to identify distinct molecular subtypes of MI, and they found several genes were significantly related to the development of MI, with being regulated by m 6 A methyltransferases. In the present research, we also observed the differences in m 6 A modification in MeRIP of MI and sham control tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Based on RNA sequencing data, long-term exposure to MPs may be related to alterations in the biological features and global gene expression patterns in mice, providing novel insights into the biological toxicity of MPs [70]. N6-methyladenosine (m6A) modifications in ncRNAs have been identified as manipulating factors in cardiovascular diseases [71,72]. Zhang et al demonstrated the N6-methyladenosine (m6A) modification profile of non-coding RNA (ncRNAs) in myocardial tissues exposed to MP using RNA sequencing (RNA-seq) and methylated RNA immunoprecipitation sequencing (MeRIP-seq).…”
Section: Toxicities In Other Animal Cellsmentioning
confidence: 99%
“…36 The RNA m 6 A modification by methyltransferase METTL3 drives proliferation, differentiation, and ECM accumulation in cardiac fibroblasts, 150 as well as wider cardiac remodelling. 151 Other means of transcriptional influence, such as RBPs, also regulate fibrotic progression. Indeed, ∼30% of TGFβ driven genes are translationally regulated independent of transcript abundance, with PUM2 and QKI required for fibroblast activation.…”
Section: Intracellular Regulationmentioning
confidence: 99%
“…Furthermore, epigenetic modifications including DNA methylation, histone acetylation, and RNA methylation (m 6 A) are emerging as direct effectors of fibrogenesis 36 . The RNA m 6 A modification by methyltransferase METTL3 drives proliferation, differentiation, and ECM accumulation in cardiac fibroblasts, 150 as well as wider cardiac remodelling 151 . Other means of transcriptional influence, such as RBPs, also regulate fibrotic progression.…”
Section: Understanding Complexities In Cardiac Fibrosismentioning
confidence: 99%